Respuesta :
Answer:
We have the function cos(x)*(cos(x) + 1) = 0
Here we have two sides of an equation:
if cos(x) = 0, then the equation is equal to zero (because this therm is multiplicating the whole equation), so the values pi/2, 3pi/2, etc, are solutions.
And if the parentheses is zero, (cos(x) + 1) = 0 then the equation is also zero
Then when cos(x) = - 1 is another solution
This means that x = pi, 3pi, etc.
Answer:
X=pi/2+-2piN,x=3pi/2+-2piN,x=Pi +-2piN
Step-by-step explanation:
Just did on ap€x